Effect of Noise Stress Exposusre on Heart Histopathology of White Rat (Rattus Norvegicus) (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2024)
Noise is one of stressors that can occur over a long period and adversely affect health if it exceeds the ability to adapt. The heart plays a significant role and is the main organ in distributing oxygen, substances, minerals, and other organic substances in the blood. The samples used in this study amounted to 24 white male rats divided into four groups. Group K1 is a control rat that does not give treatment, Group P1 is given noise treatment for 6 hours of exposure, Group P2 with 9 hours of exposure, and Group P3 with a dose of 12 hours of exposure. Heart samples were collected and histology preparations were obtain by Hematoxylin-Eosin (HE) staining, and microscopic observe were made with 10μm and 40μm magnification. The results of the study were then adjusted to degree of damage and analyzed using the Kruskall-Wallis test and the Mann-Whitney test to showing changes in the form of necrosis and inflammation due to noise stress with different levels of damage and obtained a value below the critical value (p